2020
DOI: 10.1177/0003489420950364
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in Laryngoscopy Analysis: A Proof of Concept Observational Study for the Identification of Post-Extubation Ulcerations and Granulomas

Abstract: Objective: Computer-aided analysis of laryngoscopy images has potential to add objectivity to subjective evaluations. Automated classification of biomedical images is extremely challenging due to the precision required and the limited amount of annotated data available for training. Convolutional neural networks (CNNs) have the potential to improve image analysis and have demonstrated good performance in many settings. This study applied machine-learning technologies to laryngoscopy to determine the accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…To address this problem, computer-assisted diagnosis (CAD) with deep learning technique has been implemented in laryngoscopy. [2][3][4][5][6][7][8] It has been demonstrated that deep neural networks (DNNs) can be applied to laryngoscopic images to discriminate between two diseases (i.e. binary classification).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this problem, computer-assisted diagnosis (CAD) with deep learning technique has been implemented in laryngoscopy. [2][3][4][5][6][7][8] It has been demonstrated that deep neural networks (DNNs) can be applied to laryngoscopic images to discriminate between two diseases (i.e. binary classification).…”
Section: Introductionmentioning
confidence: 99%
“…binary classification). 2,3,6 Other studies reported outstanding results in discriminating laryngeal neoplasms (benign, precancerous lesions, and cancer) compared to clinicians' visual assessment. 7,8 However, many studies on the laryngeal image classification focused only on specific diseases and are limited in their applicability to real clinical practice for diagnosing various laryngeal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a semantic segmentation approach was taken, which yielded in dice similarity coefficient of 0.78 ± 0.24 and 0.75 ± 0.26 on retrospective and prospective test sets, respectively. Similarly, for the laryngoscopy 74 , various lesions were annotated in 127 images from 25 patients to train a UNet architecture showing per-pixel sensitivity of 82% and for granulomas and 62.8% for ulceration. Segmentation of recurrent laryngeal nerve, responsible for human speech, during surgery (thyroidectomy) was achieved using the widely known mask R-CNN (instance segmentation) approach 75 .…”
Section: Methodsmentioning
confidence: 99%
“…AI in other endoscopic procedures. Some other types of endoscopic images-based deep learning applications include (a) detection of nasopharyngeal malignancies 73 , and segmentation of granulomas and ulcerations on images acquired by laryngoscopy 74 , (b) an end-to-end deep learning algorithm to segment and measure laryngeal nerves during thyroidectomy (a surgical procedure) 75 , and (c) deep-learning-based anatomical interpretation of video bronchoscopy images 76 . A recent review and metaanalysis paper on laryngeal endoscopy 77 suggested the AI models presented high overall accuracy between 0.806 and 0.997.…”
Section: Metrics Used For the Evaluation Of Methodsmentioning
confidence: 99%
“…Only in recent years has there been a constant rise in publications of articles investigating the application of AI in laryngoscopic images. Although we did not performed a systematic review of literature, a thorough literature search revealed over 15 publications in the last 6 years 16–32 . A rough summary of these articles showed that all but one research group investigated still images (i.e., photos) of laryngeal lesions in a postprocessing method.…”
Section: Introductionmentioning
confidence: 99%